PENGARUH KECERDASAN EMOSIONAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. BTPN SYARIAH CABANG AREA CIREBON TIMUR - Agus Yudianto; Tika Indah Septyana (BBM (Buletin Bisnis & Manajemen), 2018)
Problems in this study is whether or not the influence of emotional intelligence on employee productivity at PT. BTPN Syariah Branch Area East Cirebon, which is identified from emotional intelligence.This study aims to obtain data about the effect of emotional intelligence on employee productivity at PT. BTPN Syariah Branch Area East Cirebon. Research Methods in this research is descriptive method and survey. Population in this research counted 35 people with sample used in this research counted 35 people by using census technique. The test in this research is based on validity test, reliability test, normality test, homogeneity test, linearity test, simple regression test.The results showed the positive and significant influence of emotional intelligence on employee productivity at PT. BTPN Syariah Branch Area East Cirebon. The magnitude of the effect of emotional intelligence on employee productivity is shown by the value of R Square of 0.615 or 61.5%. Emotional intelligence of PT. BTPN Syariah Branch East Cirebon Area is in the high category (48.57%) and very high (40%); Nor is the productivity of employees at PT. BTPN Syariah Branch Area East Cirebon is in the high category of 28.57% and very high category of 25.71%.Overall, it can be concluded that this research has successfully revealed the effect of emotional intelligence on work productivity of employees in PT. BTPN Syariah Branch Area East Cirebon. Thus, the higher the emotional intelligence of an employee, the higher the work productivity. Keywords: Emotional Intelligence, Employee Productivity